DEVELOPMENT OF LEGAL REGULATION FOR DRONE AS UNMANNED AIRCRAFT IN LATVIA - Bite, Kitija (Administrative and Criminal Justice, 2016)
In this article the author examines existing and seldom researched issues regarding the legal framework for regulating unmanned aircraft flights, focussing particularly on drone flights. The purpose of the article is to analyse the existing and draft legal framework for regulating unmanned aircraft flights, identifying issues pertaining to drone flight legal regulation and recommending solutions. The author analyses the notion of unmanned aircraft flights, the existing legal framework, draft legal framework and raises concerns regarding the future of drone flights. Currently, there is no definition for unmanned aircraft and drones. The definition is included in the draft provisions; however, the author concludes that this definition can cause problems when trying to extend the rules for drones. For this reason, the author offers to clarify the definition for unmanned aircraft flights which is included in the draft framework. It is necessary to clarify the law "On Aviation" rules, including human rights as threatened interests of unmanned aircraft flights. The author proposes introducing all unmanned aircraft registration and training of unmanned aircraft before obtaining a license. The author also proposes introducing a new profession in the future – drone pilot – for which it would be mandatory to earn a drone pilot license.